Kontrola efektywności zarządzania kadrami w przedsiębiorstwach międzynarodowych - Kowalczyk, Stanisław (Control of HR efficiency in international companies, 2006)
The author presents the results of the research on foreigners’ participation in control over management processes in some international companies operating in Poland, as well as on relationships among these companies and their head offices in personnel function control process. The analysis presents that nowadays the level of foreigners’ participation has significantly decreased compared to the beginning of their activity in Poland. It also shows that in majority of corporations personnel function control is either managed by the corporation head office, according to the common standards, or is performed independently, according to the standards worked out in the company. HR scorecard was also presented in this article as a new approach to evaluation of HR efficiency in international companies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 242-248